GP19 Methotrexate neurotoxicity: MRI changes in children with ALL. (June 2019) - Haddick, Anne; McCarthy, Anthony; Macartney, Christine
Abstract : Background: Acute lymphoblastic leukaemia (ALL) is the commonest childhood malignancy in Europe. The survival rate has dramatically increased due to advances in treatment and it is of extreme importance to optimise and individualise treatment for each child. A crucial drug in this treatment is methotrexate. This can be given through the oral, intravenous and intrathecal route. However, methotrexate has various side effects, particularly neurotoxicity. MRI typically shows white matter changes known as leukoencephalopathy. The aim of this study was to look at the MRI changes in these patients and to determine persistence of neurological effects. Method: A retrospective study looking at patients, treated for ALL, on UK ALL 2003 and 2011 trials in a single centre who developed Methotrexate Neurotoxicity were selected. Parameters including type of symptoms, length of symptoms, and timing from last Methotrexate dose were correlated with MRI findings. Results: There were 6 patients out of 138 enrolled on study who were diagnosed with neurotoxicity following MTX treatment. The age ranged from 4–11 years old with a mean age of 7. All 6 patients had MRIs. 2 patients had changes on their scans. White matter changes were displayed consistent with leukoencephalopathy. Both patients have been followed up in clinic and have no further neurological deficit. There have been no reports of further neurological deficit in the other 4 patients. Novel findings in this study found that patients with MRI changes also showed generalised changes on their EEG. Conclusions: This study describes the clinical course and radiological findings of patients with Methotrexate-induced Leukoencephalopathy. This appears to be a reversible entity without any apparent long-term effects. Long term follow-up and evaluation will be necessary to confirm this. Prospective add-on studies are warranted to evaluate this issue in a more robust manner.